Kinesin-2 family in vertebrate ciliogenesis - Zhao, Chengtian (National Academy of Sciences, 2012)
The differentiation of cilia is mediated by kinesin-driven transport. As the function of kinesins in vertebrate ciliogenesis is poorly characterized, we decided to determine the role of kinesin-2 family motors—heterotrimeric kinesin-II and the homodimeric Kif17 kinesin—in zebrafish cilia. We report that kif17 is largely dispensable for ciliogenesis; kif17 homozygous mutant animals are viable and display subtle morphological defects of olfactory cilia only. In contrast to that, the kif3b gene, encoding a heterotrimeric kinesin subunit, is necessary for cilia differentiation in most tissues, although exceptions exist, and include photoreceptors and a subset of hair cells. Cilia of these cell types persist even in kif3b/kif17 double mutants. Although we have not observed a functional redundancy of kif3b and kif17, kif17 is able to substitute for kif3b in some cilia. In contrast to kif3b/kif17 double mutants, simultaneous interference with kif3b and kif3c leads to the complete loss of photoreceptor and hair cell cilia, revealing redundancy of function. This is in agreement with the idea that Kif3b and Kif3c motor subunits form complexes with Kif3a, but not with each other. Interestingly, kif3b mutant photoreceptor cilia differentiate with a delay, suggesting that kif3c, although redundant with kif3b at later stages of differentiation, is not active early in photoreceptor ciliogenesis. Consistent with that, the overexpression of kif3c in kif3b mutants rescues early photoreceptor cilia defects. These data reveal unexpected diversity of functional relationships between vertebrate ciliary kinesins, and show that the repertoire of kinesin motors changes in some cilia during their differentiation.